Answer:
? = 16
Explanation:
x2 - 8x + ? = 42 + ?
1. Take the coefficient of the middle term 8x, which is 8 and divide it by 2.
. Then square it
2. Take 16 and add it to both sides:
![x^2 - 8x + 16 = 42 + 16](https://img.qammunity.org/2022/formulas/mathematics/college/7235wt007snts5b272eipxf3qbjx1kgogf.png)
2. Take half of the coefficient 8 that you divided by 2, which is 4 and insert 4 into the equation
![(x -4)^2 = 58](https://img.qammunity.org/2022/formulas/mathematics/college/zg0eyw9h7f6vetax6s1xr7xm6fgdcpaya1.png)
3. ? = 16